Spectrophotometric and conductometric studies of molecular interaction of brilliant cresyl blue with cationic, anionic and non-ionic surfactant in aqueous medium for application in photogalvanic cells for solar energy conversion and storage - Chandrakanta Mall; Prem Prakash Solanki (Energy Reports, 2018)
Dye-surfactant interaction in aqueous solutions is of a great importance in technology of dyeing and electrochemical devices such as solar heaters, photovoltaic cell, photogalvanic cell etc. The interaction of the cationic oxazine dye (brilliant cresyl blue, BCB) with anionic (sodium lauryl sulphate, SLS), cationic (hexadecyltrimethylammonium bromide, CTAB) and nonionic (tween 80) surfactants were studied by spectrophotometric and conductometric methods. This study was based on the effect of nature of surfactants on dye-surfactant complex formation. In spectrophotometric study, an absorbance maximum (λmax) for only BCB solution was observed 624.5 nm at lab temperature. The λmax value of BCB was shifted towards higher wavelength (644.5 nm) with SLS and towards lower wavelength (517.5 nm) with tween 80. But, there was no any type of shifting was observed with CTAB. The shifting in λmax value of BCB is due to the complex formation of BCB with SLS and tween 80. These results were supported by conductometric study in which the specific conductance of BCB with SLS and tween 80 mixed solutions were decreased in comparison to sum of individual BCB, SLS or tween 80 while no change was observed with CTAB at 25, 30, and 35 êC. The decrease in specific conductance was caused by the complex formation of slow moving or non-moving larger dye-surfactant complex. The result shows that BCB form complex with SLS and tween 80; however, no complex forms with CTAB. Spectrophotometric study gives information about the stability as well as interaction while conductometric data informs only interaction of BCB with different surfactants. The order of interaction of BCB with different surfactants from both methods are: BCB-tween 80 >BCB-SLS >BCB-CTAB while the order of stability from spectrophotometric method is: BCB-SLS >BCB-CTAB >BCB-tween 80. Therefore, the cationic dye which shows red shift with surfactant might be more useful comparison to which shows blue shift with surfactant for improvement of electrical output of photogalvanic cell. The stability order of dye-surfactants is strongly supported to the order of electrical output of already reported data of photogalvanic cells. Hence, this type of interaction plays an important role for enhancement of electrical output of the photogalvanic cells for solar energy conversion and storage.
Keywords: 330; Brilliant cresyl blue; Conductometric method; Dye-surfactant interaction; Hexadecyltrimethylammonium bromide; Photogalvanic cells; Sodium lauryl sulphate; Spectrophotometric method; Tween 80